Approaches to wh-structures in Turkish - Arslan, Zekiye Ceyda. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1999., 1999)
The aim of this study is to analyze and account for the syntactic properties of wh-structures in Turkish within the Government and Binding framework. Wh-constituents in a Turkish interrogative sentence occurs ttin situ", i.e. in the position where a non-question word with the same grammatical function would occur in the corresponding declarative structure. However, the fact that the wh-element can take the matrix scope without undergoing syntactic movement to clause initial position has led to the assumption that Turkish wh-structures undergo a movement rule at the level of Logical Form (Akar, 1990; Ozsoy, 1990). This study presents arguments for a non-raising analysis: of wh-structures in Turkish. It discusses that the LF wh-movement analysis fails to account for the occurrence of adjunct wh-elements within a sentential subject and a postpositional phrase, and further argues that the interpretation of scope interaction of quantifier phrases, wh-constituents and the operator yalnlZca tonly' is left unexplained. The explanation to these structures is offered along the lines of the wh-indexing analysis proposed by Aoun and Li (1993) who claim that wh-elements in situ do not undergo movement at any syntactic level, but instead, get coindexed with a Qu(estion) operator in the [Spec, CP] position of the clause they have scope over. The function of this Qu operator is to bind and provide an antecedent for the wh-element in situ which thus reflects its scopal properties.
Keywords: Turkish language -- Grammar.; Turkish language -- Interrogative.